Long-term trends in the clinical management and outcomes of patients with gastroesophageal cancer in Norway - Alexander Kolstad; Gabrielle Emanuel; Geir Olav Hjortland; Yngvar Nilssen; Maria Ulvestad; Ali Areffard; Eirik Kjus Aahlin (Acta Oncologica)
Background and purpose: Gastroesophageal cancers are highly prevalent internationally, with many patients diagnosed with metastatic disease, leading to challenging treatment and poor survival. This study uses real-world evidence from a population-level database to describe demographics, clinical characteristics, initial treatment patterns, and survival for patients with gastroesophageal cancer in Norway.